2018
DOI: 10.18551/rjoas.2018-08.60
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Light Intensity and Paclobutrazol on Flowering of Lantana Plants (Lantana Camara L.)

Abstract: Lantana camara L. widely planted in the city park as a bedding plant. Lantana grows in shaded place will experiencing stem elongation (etiolation) and decrease the number of flowers. This study use Nested Design that examined the effect of light intensity combined with four concentration of paclobutrazol with three replications. The results show that there was reduction of light intensity up to 50% with the addition of 80 ppm paclobutrazol concentration could inhibit plant length and increase the number of flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Lantana is an ornamental plant planted in garden and parks .The elegant floral colors of Lantana include white, yellow, blue, purple and red. Lantana plants do not grow well in shaded areas because lantana needs a location with high light intensity (Muthahara et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Lantana is an ornamental plant planted in garden and parks .The elegant floral colors of Lantana include white, yellow, blue, purple and red. Lantana plants do not grow well in shaded areas because lantana needs a location with high light intensity (Muthahara et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the natural environment, the lantana wild cultivar produces more flowers in full sun than grown in shaded environments with low LI. It has been reported that wild cultivars showed a direct correlation between LI and flowering (MUTHAHARA et al, 2018;GOYAL & SHARMA, 2019). In the present study, the LIs studied (W90 and W135) are considered low when compared to a natural light environment, even in shade.…”
Section: Introductionmentioning
confidence: 76%
“…Plants grown under 50% shade (1048 µmol m −2 s -1 ) showed twice the vegetative growth as compared to those grown under complete sunlight (2329 µmol m −2 s -1 ). Conversely, while comparing plants grown under full sun and 25% shading (1668 µmol m −2 s -1 ), no significant difference was observed in plant height (MUTHAHARA et al, 2018;GUNASEKARA & RANWALA, 2018). In the present research, the effective LIs were 146 µmol m −2 s -1 (W90) and 219 µmol m −2 s -1 (W135), with plants receiving approximately 50-70 µmol m −2 s -1 (W90) and 70-90 µmol m −2 s -1 (W135), respectively.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The application of paclobutrazol 80 ppm at a light intensity of 75% and 50% gives the same leaf color as the light intensity treatment of 100% and paclobutrazol 0 ppm. At the age of 84 dap the decrease in light intensity of 75% and 50% is able to change the color of the leaves of the coleus plant to be more faded (Muthahara et al, 2018). At paclobutazol concentrations of 0 ppm and 40 ppm, the color of the leaves of the coleus plant fades to Dark Pink Red 53 C, while at paclobutrazol concentrations of 80 ppm and 120 ppm the decrease in light intensity is 75% to 50% each of them is able to increase the brightness and concentration of the red color of the leaves of the coleus plant to Dark Purple Red 59 B and Dark Purple Red 59 A.…”
Section: Leaf Colormentioning
confidence: 99%